Determining socially optimal nitrogen application rates using a delayed response model: the case of irrigated corn in western Kansas - Nkonya, Ephraim M.; Featherstone, A. M. (2000)
Nitrate contamination of groundwater is an important problem. The transport of leached nitrate from the root zone to groundwater takes approximately 30 to 60 years. Many previous studies ignore this time lag by assuming instantaneous contamination. This analysis applies a delayed response model to account for the time lag between nitrogen fertilizer applications to the time the leached nitrate reaches groundwater. Results show that accounting for the leached nitrate externality reduces the nitrogen application rate by 13% and the returns above variable costs by 8% for farmers who apply both nitrogen and phosphorus. For farmers who do not use phosphorus, nitrogen use is reduced by 14% and the returns above variable costs by 22%. The application of phosphorous increased returns by more than 100% and significantly reduced leached nitrate.